Analysis of Counseling Implementation by Pharmacists in Community Pharmacies - Thalia Khandy, Evanda Ratna; Utami, Wahyu; Rahem, Abdul (Jurnal Keperawatan Silampari, 2024)
This study aims to analyze the factors that influence the implementation of pharmacist counseling in community pharmacies in Malang Regency. This research method is an observational study, with a cross-sectional design. Data analysis shows a significant relationship (p <0.05) between each independent variable and the implementation of counseling. In conclusion, the availability of facilities and infrastructure has the strongest influence on the implementation of pharmacist counseling, followed by attitudes, knowledge, and policies. Keywords: Pharmacist, Pharmacy, Counseling, Pharmaceutical Services